Do higher primary care practice performance scores predict lower rates of emergency admissions for persons with serious mental illness? An analysis of secondary panel data - Rowena Jacobs; Nils Gutacker; Anne Mason; Maria Goddard; Hugh Gravelle; Tony Kendrick; Simon Gilbody; Lauren Aylott; June Wainwright (National Institute for Health Research, 2015)
Background: Serious mental illness (SMI) is a set of chronic enduring conditions including schizophrenia and bipolar disorder. SMIs are associated with poor outcomes, high costs and high levels of disease burden. Primary care plays a central role in the care of people with a SMI in the English NHS. Good-quality primary care has the potential to reduce emergency hospital admissions, but also to increase elective admissions if physical health problems are identified by regular health screening of people with SMIs. Better-quality primary care may reduce length of stay (LOS) by enabling quicker discharge, and it may also reduce NHS expenditure. Objectives: We tested whether or not better-quality primary care, as assessed by the SMI quality indicators measured routinely in the Quality and Outcomes Framework (QOF) in English general practice, is associated with lower rates of emergency hospital admissions for people with SMIs, for both mental and physical conditions and with higher rates of elective admissions for physical conditions in people with a SMI. We also tested the impact of SMI QOF indicators on LOS and costs. Data: We linked administrative data from around 8500 general practitioner (GP) practices and from Hospital Episode Statistics for the study period 2006/7 to 2010/11. We identified SMI admissions by a main International Classification of Diseases, 10th revision (ICD-10) diagnosis of F20-F31. We included information on GP practice and patient population characteristics, area deprivation and other potential confounders such as access to care. Analyses were carried out at a GP practice level for admissions, but at a patient level for LOS and cost analyses. Methods: We ran mixed-effects count data and linear models taking account of the nested structure of the data. All models included year indicators for temporal trends. Results: Contrary to expectation, we found a positive association between QOF achievement and admissions, for emergency admissions for both mental and physical health. An additional 10% in QOF achievement was associated with an increase in the practice emergency SMI admission rate of approximately 1.9%. There was no significant association of QOF achievement with either LOS or cost. All results were robust to sensitivity analyses. Conclusions: Possible explanations for our findings are (1) higher quality of primary care, as measured by QOF may not effectively prevent the need for secondary care; (2) patients may receive their QOF checks post discharge, rather than prior to admission; (3) people with more severe SMIs, at a greater risk of admission, may select into practices that are better organised to provide their care and which have better QOF performance; (4) better-quality primary care may be picking up unmet need for secondary care; and (5) QOF measures may not accurately reflect quality of primary care. Patient-level data on quality of care in general practice is required to determine the reasons for the positive association of QOF quality and admissions. Future research should also aim to identify the non-QOF measures of primary care quality that may reduce unplanned admissions more effectively and could potentially be incentivised. Funding: The National Institute for Health Research Health Services and Delivery Research programme.